Puffling patrol - Lewin, Ted (Lee & Low Books, 2012)
"Ted and Betsy Lewin detail the annual rescue of baby puffins by the children of Heimaey, the largest island in the Westman Islands off the coast of Iceland. Includes additional information about puffins and the Westman Islands, glossary, and further reading"--Provided by publisher.